Manajemen Museum dan Situs Kepurbakalaan Banten Lama Kota Serang - Hasanah, Budi (Universitas Serang Raya, 2015)
The pupose of this research aims to determine the management of the museum and the archeological site of Banten Lama at the moment that have been conducted by technical Implementation Unit (UPT) of Serang Cultural Preservation House. This research approach used qualitative with descriptive method. To determine the fenomenon about the management of the museum and the archeological site of Banten Lama withe used George R Terry theory that included by 4 (four) function of management that is planing, organizing, actuating, and controlling. The result showed the management activities of Banten Lama museum and site in the process of planning, organizing, actuating, controlling are not yet optimal.